ANALISIS PENGARUH KOMPENSASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Penjualan PT. Great Mataram Semarang) - Prakoso, Bagas Adi; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2015)
Human resources has becoming one of the most vital factor that determine the company’s success. The company’s success itself is usually determined by the employee’s performance. Pre survey result has found a phenomenon which occurs in the company is a decreasing on the employee’s performance. On the other hand there are previous research about the influence of the compensation and leadership on employee performance. This is the background for this research.This research is using compensation and leadership as the independent variable and employee’s performance as the dependent variable. The population of this research are marketing division of PT. Great Mataram Semarang. Sampling technique used in this research is sensus, with 45 correspondent. Reliability and validity of this data has been tested with validity and reliability test. This research is using multiple linear regression method.The multiple linear regression shown that compensation and leadership have positive significant impact to the employee’s performance. The coefficient determination shown that compensation and leadership affecting marketing division’s performance by 59,5%. While the other 40,5% are determined by another variable that is not explained in this research.